Loss of PTPN22 Promotes Intestinal Inflammation by Compromising Granulocyte-mediated Antibacterial Defence. (5th June 2021) - Spalinger, Marianne R; Schwarzfischer, Marlene; Niechcial, Anna; Atrott, Kirstin; Laimbacher, Andrea; Gottier, Claudia; Lang, Silvia; Scharl, Michael
Abstract: Background and aims: A single nucleotide polymorphism in protein tyrosine phosphatase non-receptor type 22 [PTPN22] has been associated with the onset of autoimmune disorders, but protects from Crohn's disease. PTPN22 deficiency in mice promotes intestinal inflammation by modulating lymphocyte function. However, the impact of myeloid PTPN22 in colitis development remains unclear. The aim of this study was to investigate the role of PTPN2 in the IL-10 and the T cell transfer colitis models. Methods: PTPN22-deficient mice were crossed with IL-10-/- and RAG2-/- mice. Naïve T cells were injected in RAG-/- mice to induce T-cell transfer colitis. Spontaneous colitis in IL-10-/- mice was monitored for up to 200 days. Results: Here, we demonstrate that PTPN22 in non-lymphoid immune cells is required to protect against T cell transfer-mediated and IL-10 knock-out colitis. Analysis of the intestinal immune landscape demonstrated a marked reduction of granulocyte influx into the inflamed colon in PTPN22-deficient mice. On a molecular level, granulocytes were not only reduced by numbers, but also revealed a defective function. In particular, granulocyte activation and granulocyte-mediated bacteria killing was impaired upon loss of PTPN22, resulting in elevated bacterial burden and translocation beyond the intestinal epithelial barrier in PTPN22-deficient mice. Consistently, antibiotic-induced depletion of bacteria reverted the increased colitis susceptibility in PTPN22-deficient mice, whereas granulocyte depletion induced acolitis phenotype in wild-type mice similar to that observed in PTPN22-deficient mice. Conclusions: In conclusion, our data demonstrate that PTPN22 is essential for adequate granulocyte activation and antimicrobial defence to protect the inflamed intestine from bacterial invasion and exacerbated colitis.